Efektivitas Terapi Ultrasound Pada Penanganan Carpal Tunnel Syndrome - Muhammad Imam Dzuhdi; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Carpal Tunnel Syndrome (CTS) is a common median nerve compression neuropathy that causes pain, tingling, and impaired hand function. Various conservative approaches have been used, including ultrasound therapy, nerve-gliding exercises, phonophoresis, and ultrasound-guided injection techniques. This literature review aims to examine the effectiveness of ultrasound-based interventions in the management of mild to moderate CTS. Methods: This review analyzed eight Randomized Controlled Trial (RCT) studies published between 2021 and 2025. The literature sources were obtained from international journals indexed in Scopus (Q1–Q3). The evaluated outcome parameters included pain (VAS), hand function (BCTQ-SSS/FSS), nerve conduction (ENMG, DML, SNCV), and median nerve cross-sectional area (CSA). Results: Most studies reported that ultrasound-based interventions—either as a therapeutic modality (underwater ultrasound, phonophoresis, or combined with exercise) or as guidance for injection procedures (hydrodissection and transverse carpal ligament release)—produced significant improvements in symptoms and hand function. The combination of ultrasound with splinting and exercise therapy yielded superior outcomes compared to single-modality treatment. Ultrasound-guided hydrodissection also demonstrated improvements in nerve parameters and symptom reduction in the medium term (6–12 months). Conclusion: Ultrasound therapy is effective, safe, and relevant as both a conservative and minimally invasive interventional approach for managing mild to moderate CTS. Its combination with exercise or nerve-gliding techniques enhances clinical and electrophysiological outcomes.